A New Family of Anionic FeIII Spin Crossover Complexes Featuring a Weak‐Field N2O4 Coordination Octahedron. Issue 4 (21st December 2015) - Takahashi, Kazuyuki; Kawamukai, Kiko; Okai, Mitsunobu; Mochida, Tomoyuki; Sakurai, Takahiro; Ohta, Hitoshi; Yamamoto, Takashi; Einaga, Yasuaki; Shiota, Yoshihito; Yoshizawa, Kazunari
Abstract: Unprecedented anionic Fe III spin crossover (SCO) complexes involving a weak‐field O, N, O‐tridentate ligand were discovered. The SCO transition was evidenced by the temperature variations in magnetic susceptibility, Mössbauer spectrum, and coordination structure. The DFT calculations suggested that larger coefficients on the azo group in the HOMO−1 of a ligand might contribute to the enhancement of a ligand‐field splitting energy. The present anionic SCO complex also exhibited the light‐ induced excited‐spin‐state trapping effect. Abstract : Photoinduced spin transition : Unprecedented anionic spin crossover (SCO) complexes involving a weak‐field Fe III N2 O4 coordination sphere were discovered. The tetramethylammonium salt of the depicted SCO anion exhibited the light‐induced excited‐spin‐state trapping effect, which is quite rare in Fe III SCO complexes (see scheme).